Esophageal wound healing by aligned smooth muscle cell-laden nanofibrous patch - Miji Yeo; Jung Won Yoon; Gyu Tae Park; Sung-Chan Shin; Young-Cheol Song; Yong-Il Cheon; Byung-Joo Lee; Geun Hyung Kim; Jae Ho Kim (Materials Today Bio, 2023)
The esophagus exhibits peristalsis via contraction of circularly and longitudinally aligned smooth muscles, and esophageal replacement is required if there is a critical-sized wound. In this study, we proposed to reconstruct esophageal tissues using cell electrospinning (CE), an advanced technique for encapsulating living cells into fibers that allows control of the direction of fiber deposition. After treatment with transforming growth factor-β, mesenchymal stem cell-derived smooth muscle cells (SMCs) were utilized for cell electrospinning or three-dimensional bioprinting to compare the effects of aligned micropatterns on cell morphology. CE resulted in SMCs with uniaxially arranged and elongated cell morphology with upregulated expression levels of SMC-specific markers, including connexin 43, smooth muscle protein 22 alpha (SM22α), desmin, and smoothelin. When SMC-laden nanofibrous patches were transplanted into a rat esophageal defect model, the SMC patch promoted regeneration of esophageal wounds with an increased number of newly formed blood vessels and enhanced the SMC-specific markers of SM22α and vimentin. Taken together, CE with its advantages, such as guidance of highly elongated, aligned cell morphology and accelerated SMC differentiation, can be an efficient strategy to reconstruct smooth muscle tissues and treat esophageal perforation.